Correction to: Invasive group A Streptococcus disease in Australian children: 2016 to 2018 - a descriptive cohort study - Jane Oliver; Elise Thielemans; Alissa McMinn; Ciara Baker; Philip N. Britton; Julia E. Clark; Helen S. Marshall; Christopher C. Blyth; Joshua Francis; Jim Buttery; Andrew C. Steer; Nigel W. Crawford; et al. (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.